The Experience of Symptom Cluster and Symptom Alleviation Self-Care in Patients with Head and Neck Cancer: A Qualitative Study - Wyssie Ika Sari; Suhartini Ismail (Faculty of Nursing Universitas Padjadjaran, 2019)
Patients with head and neck cancer usually experience physical and psychological changes and adjustments related to the disease and management of therapy. The patients will experience symptom cluster and will use effective symptom alleviation self-care to relieve the symptoms. The proper identification of symptom cluster and the effectiveness of using symptom alleviation self-care will be the basis for the success of disease management. This study aimed to investigate the symptom cluster and symptom alleviation self-care in patients with head and neck cancer, and which has an impact on the quality of life. This research was a pilot study using a qualitative design and involved five patients at the public hospital in Semarang, Indonesia. The qualitative design has been chosen to explore the varied of symptom experienced by the patients about the nature, number, location, duration and intensity of experiences, which may different experiences of symptom cluster and symptom alleviation self-care for each patient with Head and Neck Cancer. Data were collected through semi-structured interviews and analyzed used the qualitative content analysis process. Three themes were identified in this study, including: the patients’ experience of symptom cluster, the patients’ experience of symptom alleviation self-care, and the impaired quality of life domain. The results of this study showed that the patients’ experience sickness and gastrointestinal symptom cluster during illness and undergoing therapy, as well as variations in the symptom alleviation self-care, including: diet/ nutrition/ lifestyle changes, mind/ body/ spiritual control, biological treatment, herbal treatment, and prescribed medicine. The symptom cluster and symptom alleviation self-care has an impact on the patients’ outcome that is the quality of life. This study showed that the experience of symptom cluster and symptom alleviation self-care varied and highly individualized, which has an impact on the quality of life. The importance of proper identification about symptom cluster and the effectiveness of using symptom alleviation self-care by the nurses will be the basis for the success of disease management to improve the patients’ quality of life. Therefore, optimizing the nurses’ role is needed as the basis for the development of symptom management nursing programs.